2014
DOI: 10.1213/ane.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Model Predictions of Wake-Up Time During Scoliosis Surgery

Abstract: The results confirmed our study hypothesis; a sevoflurane-remifentanil interaction model built from observations in volunteers and adapted to desflurane and fentanyl accurately predicted patient response during a wake-up test. These results were similar to our previous study comparing model predictions and patient observations after a sevoflurane-remifentanil/fentanyl anesthetic. The OAA/S <2 model most accurately predicted the time patients would respond by moving their fingers and toes. This model may help a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The authors hypothesised that the interaction models would accurately predict return of responsiveness during a wake‐up test. Their results confirmed the study hypothesis, and suggested that this modelling may help anaesthetists to more accurately predict return of responsiveness during a wake‐up test in patients undergoing spine surgery .…”
Section: Other Applicationssupporting
confidence: 63%
“…The authors hypothesised that the interaction models would accurately predict return of responsiveness during a wake‐up test. Their results confirmed the study hypothesis, and suggested that this modelling may help anaesthetists to more accurately predict return of responsiveness during a wake‐up test in patients undergoing spine surgery .…”
Section: Other Applicationssupporting
confidence: 63%
“…93 More recently, a study showed accurate predictions for wake-up time from a sevoflurane-remifentanil interaction model adapted to equipotent sufentanil-desflurane doses that were used. 94…”
Section: Volatile Anaesthetic-opioid Interactionsmentioning
confidence: 99%
“…Fourth, accuracy deviation of <50% was used for this study. 6 We are uncertain whether a more strict definition would improve model parameters, and the effects on correlation are unknown. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The model introduced a central concept, θ a new drug as a ratio of alfentanil (U Alf ) and midazolam (U mid ) (Equation 6). …”
Section: Minto Modelmentioning
confidence: 99%
See 1 more Smart Citation